Farm home economics - Pittman, Martha S. (My University, 1906)
Introduction: The United States has always been an agricultural nation. As growth has proceeded the suburban element has gradually wended its way westward until now, all over the country we find farms and farmer’s homes. In 1903 there were 5,739,657 farms and they have been increasing steadily since that time. Statistics say that the majority of these farms are worked by the owner himself, that his money and all his interests are expended here. For the ordinary farmer it requires most judicious management to make the money he may have cover all running expenses. This is a problem that he must needs face squarely. First, let us consider. This farm is the home so it must be home-like. The bare yards without flowers, grass or shade; rough, unpainted houses set down anywhere convenient with rubbish strewn every where are common enough to be familiar to every one. But what is the necessity? It would be just as easy to plan the house first and then build it accordingly. It might just as well be placed in some position where it could appear to advantage. There may be nothing but the smallest and plainest kind of a structure but it is worthy of at least this much attention. If paint cannot be applied a few vines will do wonders in a season and make a bower of beauty out of the most unattractive foundation.
Citation: Pittman, Martha S. Farm home economics. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Home Economics; Farms; Beautification; Theses